Twinkling effect in detecting kidney stones - Sung, Wei Pei (2014)
Statistics in recent years have shown alarming figures of patients diagnosed with kidney stones. Although the medical condition will not result in death, the possibility of recurrence increases as compared to those who have never had one. A Computed Tomography (CT) scan is usually the most effective way to detect kidney stones, since it holds a true positive rate of over 90%. The downside is the monetary costs and the exposure to harmful ionizing radiation. These factors affect the patients adversely over a period of follow-up appointments. In 1996, a mixture of colour was recorded by Rahmouni and his team of researchers under the ultrasound sonography during the detection of kidney stones. This became the medical alternative as it is cheaper than a CT scan, and comparatively non-invasive and non-radiating. However, the mechanism of this "Twinkling" phenomenon is unknown, resulting in a low sensitivity of 30% as compared to CT scan. Under the colour Doppler imaging, a blue colour is formed when an object moves away from the transducer and red represents the motion in a reciprocal direction. The twinkling effect shows a mixture of colours even when the object, being scanned, remains stationary. The main focus of this report is seeks the mechanism of this phenomenon through various experimental investigations as well as theoretical simulation so as to increase the true positive rate of renal stone detection using colour doppler imaging. Recommendations were derived through observation and directions for future studies were also included in the report.